A Comparative Study of Total Knee Arthroplasty and Unicondylar Knee Arthroplasty in the Treatment of Knee Osteoarthritis. (28th April 2022) - Wang, Lin; Wang, Qiang; Li, Qiuwei; Song, Fahuan
Abstract : Objective . To compare the clinical efficacy of total knee arthroplasty (TKA) and unicondylar knee arthroplasty (UKA) in the treatment of knee osteoarthritis (KOA). Methods . A retrospective analysis was conducted on 30 patients admitted to the Department of Orthopaedics of Yijishan Hospital from 2020 to 2021. The patients were divided into UKA group ( n = 15) and TKA group (control, n = 15). The intraoperative situation and postoperative clinical indicators of patients in the two groups were collected and compared, such as operation time, intraoperative blood loss, length of hospital stay, postoperative complications, and postoperative functional recovery. Postoperative functional recovery was investigated by the visual analogue pain scale (VAS), knee score scale (HSS), and knee range of motion (ROM) scores 5 days after surgery. Results . Perioperative indexes in the UKA group were significantly lower than those in the TKA group, including operation time, intraoperative blood loss, first time going to the ground, and length of hospital stay. VAS, HSS, and ROM scores in the two groups were significantly improved after surgery compared with those before surgery. However, ROM scores in the UKA group were significantly better than in the TKA group. In terms of early postoperative complications, there was one case of venous thrombosis of lower limbs in the UKA group, while in the TKA group there was one case of delayed wound healing due to diabetes, and one case of deep infection. Conclusion . Both UKA and TKA are very successful options for the treatment of KOA, but the use of UKA can promote the recovery of postoperative knee function, reduce postoperative complications, and achieve more satisfactory than expected results.